2017
DOI: 10.4049/jimmunol.1700340
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Murine NK Cells Degranulate and Retain Cytotoxic Function without Store-Operated Calcium Entry

Abstract: Sustained Ca signaling, known as store-operated calcium entry (SOCE), occurs downstream of immunoreceptor engagement and is critical for cytotoxic lymphocyte signaling and effector function. CD8 T cells require sustained Ca signaling for inflammatory cytokine production and the killing of target cells; however, much less is known about its role in NK cells. In this study, we use mice deficient in stromal interacting molecules 1 and 2, which are required for SOCE, to examine the contribution of sustained Ca sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition, there was a synchronized upregulation of well-characterized IFN-inducible genes, such as Irf9, Mx1 , and Isg20 . During the subsequent d2 to d4 transition, additional pathways included transcription factor NFAT signaling, which has been implicated in mediating NK cell production of IFN-γ 1214 , as well as transcription factor ATF2–AP-1 signaling and T cell-related signaling (Fig. 2d).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there was a synchronized upregulation of well-characterized IFN-inducible genes, such as Irf9, Mx1 , and Isg20 . During the subsequent d2 to d4 transition, additional pathways included transcription factor NFAT signaling, which has been implicated in mediating NK cell production of IFN-γ 1214 , as well as transcription factor ATF2–AP-1 signaling and T cell-related signaling (Fig. 2d).…”
Section: Resultsmentioning
confidence: 99%
“…In murine NK cells, it was recently reported that degranulation was persisting in the complete absence of Ca 2+ (Freund‐Brown et al . ). This finding was based on in vivo data in STIM1/2 double knock‐out NK cells and on in vitro data in the absence of [Ca 2+ ] o .…”
Section: Discussionmentioning
confidence: 97%
“…While the importance of Orai1/CRAC channel activity for cytolytic immune cell functions has been convincingly demonstrated (Lyubchenko et al 2001;Maul-Pavicic et al 2011;Schwarz et al 2013;Klemann et al 2017), there are several reports that cytotoxicity is only slightly reduced in tumour-specific murine CTLs following a drastic reduction of Ca 2+ signals by the application of 1 μM BTP2 , one of the most potent CRAC channel blockers (Zitt et al 2004). In murine NK cells, it was recently reported that degranulation was persisting in the complete absence of Ca 2+ (Freund-Brown et al 2017). This finding was based on in vivo data in STIM1/2 double knock-out NK cells and on in vitro data in the absence of [Ca 2+ ] o .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that the discrepancies in question reflect species-specific effects; we used primary murine T cells while the previous study used human material [20]. Recently, it was shown that human, but not mouse, NK cells require Ca 2+ signaling for lytic granule exocytosis [30]. Hence, it is not implausible that synaptic F-actin dynamics might be governed by different signaling constraints in human than in mouse T cells.…”
Section: Discussionmentioning
confidence: 99%